نەریتی خێڵایەتی لە روانگەی تیۆری سەرمایەی کۆمەڵایەتی لای بییر بۆردیۆ خوێندنەوەیەکی ئەنثرۆپۆلۆجیە - عبداللە, پ.د ئاسۆ ابراهیم; محمدامین, هێمن عزیز (Sulaimani Journal for Humanities, 2023)
Social capital researchers, despite their understanding and analysis of this concept, are close and similar. However, they differ in terms of the roots of its constituent elements. We will interpret, analyze and explain these views. This study aims to find out whether the tradition of tribalism represents social capital in society. In this study, an attempt has been made to describe the topics first, then analyze them theoretically within the framework of the analytical description method. Social capital has a collective characteristic, especially among people with trust, relationships and extensive social networks. In this way, preparing individuals to maintain their dominance within their social groups. Social capital theory points to the existence of tribal cultural influences in the sense that tribal groups influence the social capital of an individual within his tribal group. The tribe still represents, refers to the loyalty of tradition and the return and acquisition of its individuals within the framework of tribal tradition and associated cultural and social capital of the tribe. Keywords: culture, tradition, tribe, social capital, cultural capital.
Keywords: کلتوور نەریت خیڵ سەرمایەی کۆمەڵایەتی سەرمایەی کلتووری